1999
DOI: 10.1006/prep.1998.0983
|View full text |Cite
|
Sign up to set email alerts
|

Production of Reagents and Optimization of Methods for Studying Calmodulin-Binding Proteins

Abstract: Owing to subtle but potentially crucial structural and functional differences between calmodulin (CaM) of different species, the biochemical study of low-affinity CaM-binding proteins from Dictyostelium discoideum likely necessitates the use of CaM from the same organism. In addition, most of the methods used for identification and purification of CaM-binding proteins require native CaM in nonlimiting biochemical quantities. The gene encoding D. discoideum CaM has previously been cloned allowing production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In contrast, Rh50 and VatA did not colocalized to the CV network in apm1 Ϫ and apm1 Ϫ ϩ 1⌬Ct mutant cells ( Figure 10A). In addition, Calmodulin, another CV component (Ultricht and Soldati, 1999), also redistributed in endosomes in apm1 Ϫ cells, and the characteristic CV network was not detected in apm1 Ϫ mutant cells incubated with FM 4-64 (a fluorescent dye known to label the CV complex; our unpublished results). In addition, Calmodulin, another CV component (Ultricht and Soldati, 1999), also redistributed in endosomes in apm1 Ϫ cells, and the characteristic CV network was not detected in apm1 Ϫ mutant cells incubated with FM 4-64 (a fluorescent dye known to label the CV complex; our unpublished results).…”
Section: Ap-1 Is Required For Transport Of Proteins To the Contractilmentioning
confidence: 81%
“…In contrast, Rh50 and VatA did not colocalized to the CV network in apm1 Ϫ and apm1 Ϫ ϩ 1⌬Ct mutant cells ( Figure 10A). In addition, Calmodulin, another CV component (Ultricht and Soldati, 1999), also redistributed in endosomes in apm1 Ϫ cells, and the characteristic CV network was not detected in apm1 Ϫ mutant cells incubated with FM 4-64 (a fluorescent dye known to label the CV complex; our unpublished results). In addition, Calmodulin, another CV component (Ultricht and Soldati, 1999), also redistributed in endosomes in apm1 Ϫ cells, and the characteristic CV network was not detected in apm1 Ϫ mutant cells incubated with FM 4-64 (a fluorescent dye known to label the CV complex; our unpublished results).…”
Section: Ap-1 Is Required For Transport Of Proteins To the Contractilmentioning
confidence: 81%
“…The following antibodies were used: a mouse monoclonal antibody against the A subunit of the V-ATPase complex (VatA; monoclonal antibody, 221-35-2; Neuhaus et al , 1998) and rabbit polyclonal antibodies against Dgap1 (Faix and Dittrich, 1996), Rhesus50 (Benghezal et al , 2001), and calmodulin (Ulbricht and Soldati, 1999). The antibodies against mRFP, Sec3, and Rab8a were obtained during this study by immunization of rabbits with purified mRFP protein, purified GST-Sec3 N-terminus (amino acids [aa] 1–188), and a synthetic Rab8a peptide (aa 172–186: NH2-C-DIKKRMIDTPNEQPQ-CONH2).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were not allowed to reach a density of more than 2ϫ10 6 cells/ml. Antibodies used were a rabbit antiserum to the Cterminal cytosolic tail of Rh50 (controls showed that pFL759 was not recognized by this antiserum) ), a rabbit antiserum to calmodulin (a kind gift from T. Soldati, University of Geneva, Switzerland) (Ulbricht and Soldati, 1999) and a mouse monoclonal antibody to CsA (mAb 41-71-21) (Bertholdt et al, 1985). Note that in our cell culture conditions (low density), endogenous CsA was not expressed and therefore this anti-CsA antibody only recognized CsA-Rh50 chimeras.…”
Section: Methodsmentioning
confidence: 99%